2009
DOI: 10.1080/17290376.2009.9724931
|View full text |Cite
|
Sign up to set email alerts
|

Considering childbearing in the age of highly active antiretroviral therapy (HAART): Views of HIV-positive couples

Abstract: Objectives : Based on a qualitative study conducted in Bulawayo, Zimbabwe, this article examines how the availability of HAART since April 2004 may impact the views and choices of HIV-positive couples on childbearing. Methods : In-depth interviews were conducted with 15 couples where at least one partner was HIV positive. All respondents were of reproductive age and had or were confronting reproductive and sexual decision-making. Results : HAART seems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…The rates of participants who expressed a desire to have children (31%) and have a plan to bear a child in the near future (24%) are similar to what other studies have found in sub-Saharan Africa [1,4,812]. Furthermore, nearly one in five participants reported either parenting in the past year or about to parent a child.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The rates of participants who expressed a desire to have children (31%) and have a plan to bear a child in the near future (24%) are similar to what other studies have found in sub-Saharan Africa [1,4,812]. Furthermore, nearly one in five participants reported either parenting in the past year or about to parent a child.…”
Section: Discussionsupporting
confidence: 80%
“…Accordingly, reproductive health programs emphasize preventing pregnancies and use of contraceptives, including consistent condom use [7]. However, this approach does not account for the fact that 20–50% of PLHIV in sub-Saharan Africa want to have children [1,4,812]. Childbearing desires may at least partially explain why many PLHIV do not consistently use condoms [13,14], even in the context of serodiscordant relationships where there is a clear risk of horizontal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…This was not probed further in the current study but may reflect, first, the prominence during post-test counselling given to family planning and the need to avoid unprotected sex to prevent HIV super-infection even within concordant HIV-positive couples and, secondly, widespread awareness about the risk of mother-to-child transmission of HIV resulting from recent scale-up of programs to prevent mother to child transmission of HIV (PMTCT). Previous studies among health workers [26] and the general population [27] that have found that fear of mother-to-child transmission is common and that blame may be apportioned to pregnant women by health workers and members of the general community. However, the right to have children is enshrined under Article 16 of the Universal Declaration of Human Rights [28], and so the high rate of agreement to such a strongly worded statement is concerning and suggests that PLWHA are still subject to discrimination, albeit less crude than in the early days of recognition of the HIV epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The improved individual health through the availability of ART may result in improved sexual drive, influencing the behavior of HIV seropositive women [18]. Women on treatment may feel healthier, more optimistic about the PMTCT interventions, more positive about their own and children’s futures, and therefore engage in unprotected sexual activity and be more inclined to become pregnant [19]. …”
Section: Discussionmentioning
confidence: 99%